Odpowiedź :
5.
a) (3x-y) + (x-1) = 3x-y+x-1= 4x-y-1
b) (3x-y) + (x-1) - (-3x-y) = 3x-y+x-1+3x+y=7x-1
c) (3x-y) - (x-1) - (-3x-y) = 3x-y-x+1+3x+y=5x+1
d) (3x-y) - [(x-1) - (-3x-y)] = (3x-y) - (x-1+3x+y) = 3x-y-x+1-3x-y= -x-2y+1
7.
a) [tex]4a^{2}[/tex] -3ab= ([tex]a^{2}[/tex]+[tex]a^{2}[/tex]+[tex]a^{2}[/tex]+[tex]a^{2}[/tex]) + (-ab-ab-ab)
b) [tex]4a^{2}[/tex] -3ab= ([tex]a^{2}[/tex]+[tex]a^{2}[/tex]+[tex]a^{2}[/tex]+[tex]a^{2}[/tex]) - (ab+ab+ab)
8.
a) ([tex]4x^{2}[/tex]+4xy-7)+([tex]2x^{2}[/tex]-3xy)=[tex]6x^{2}[/tex]+xy-7
b) ([tex]5x^{2}[/tex]-4x+3) - ([tex]5x^{2}[/tex]-5x-7)=10+x
c) (18ab-7a+1)-(6ab-6a+6ab)=6ab-a+1